ANALISIS KOMUNIKASI YANG EFEKTIF PADA PT RQS - Ike Nurjanah; Christian Wiradendi; Eka Dewi Utari (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research aims to analyze the effectiveness of internal communication at PT RQS, a co- working space provider company. The method used in this research is a qualitative approach with a case study, where data collection is done through in-depth interviews and documentation. The results show that although the company has provided space for discussion through internal forums and evaluative meetings, there are still a number of significant communication barriers. These barriers include information overload conveyed through platforms such as WhatsApp, delays in providing responses, and uneven distribution of information among employees. These findings highlight the need for strengthening formal communication systems as well as improving interpersonal communication skills. We recommend that PT RQS adopt a more structured and inclusive communication strategy to support work effectiveness and team harmony.